Perbandingan Kemampuan Konsentrasi Belajar Setelah Mendengar Al-Qur’an: Antara Murattal dan Tilawah - Kautsar, Emir Surya; Damayanti, Eka; Ismail, Ilyas; Ahmad, La Ode Ismail; Jamilah, Jamilah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2020)
This study aimed at determining the differences of learning concentration ability between the students who listened to the murattal of Qur’an and the students who listened to the recitation of Qur’an. This research was a comparative study with an experimental approach using two groups pre and posttest design. There was two experimental classes and it consisted fifteen students of each. The first experimental class was given an audio murattal of the Qur’an intervention and the second experimental class was given an audio recitation of the Qur’an intervention. The data collection instruments used in this study was concentration ability tests which were developed and referenced from the Employee Aptitude Survey (EAS) test and consisted of 5 subs tests namely word fluency sub tests, verbal comprehension, verbal classification, visual space speed and accuracy test, and understanding of reading test. The results obtained in the two groups based on the t test results obtained sig. (2-tailed) 0.018 <Î± 0.05, this showed that there was a significant difference between the students who listened to murattal of the Qur’an and the students who listened recitations of the Qur’an. It appears that Qur’anic recitation treatments is more effective in increasing learning concentration